Physicochemical Control of Adult Stem Cell Differentiation: Shedding Light on Potential Molecular Mechanisms. (1st April 2010) - Titushkin, Igor; Sun, Shan; Shin, Jennifer; Cho, Michael
Abstract : Realization of the exciting potential for stem-cell-based biomedical and therapeutic applications, including tissue engineering, requires an understanding of the cell-cell and cell-environment interactions. To this end, recent efforts have been focused on the manipulation of adult stem cell differentiation using inductive soluble factors, designing suitable mechanical environments, and applying noninvasive physical forces. Although each of these different approaches has been successfully applied to regulate stem cell differentiation, it would be of great interest and importance to integrate and optimally combine a few or all of the physicochemical differentiation cues to induce synergistic stem cell differentiation. Furthermore, elucidation of molecular mechanisms that mediate the effects of multiple differentiation cues will enable the researcher to better manipulate stem cell behavior and response.